Penerapan Sistem Monitoring Biomarker Kesehatan berbasis Google Sheet untuk Meningkatkan Kesadaran Kesehatan pada Masyarakat Berisiko Metabolik di Klinik Prima Husada - Firmansyah Sumantri, Agung; Thesalonika, Lona; Alim, Agus; Nurul Huda, Ilham; Dewi Utami Hamid, Nuke; Wahab, Syaikhul; Widyaningrum, Desy; Irma Suryani, Ade; Arif Setyawan, Adhita (LPPM Politeknik Piksi Ganesha, 2024)
Changes in modern lifestyles, which tend to be sedentary, have increased theprevalence of metabolic diseases such as diabetes mellitus, hypertension, anddyslipidemia in urban communities. Regular monitoring of health biomarkersis an important step in the early detection of metabolic risks. However,the limited availability of simple and easy-to-use monitoring facilitieshas resulted in low public awareness of their health conditions.This Community Service Activity (PKM) aims to increase awarenessof health among people at risk of metabolic disorders through the implementation of aGoogle Sheet-based biomarker monitoring system at the Prima Husada Clinic in Bandung. The methodsused in this activity include socialization, training in the use of Google Sheet HealthTracker, and evaluation of health awareness levels and changes inbiomarker parameters (blood pressure, BMI, blood sugar levels, and cholesterol). The resultsof the activity showed a 52% increase in participants' understanding of the importance ofhealth monitoring, and 68% of participants began to routinely recordhealth indicators for one month. The Google Sheet system proved to be effective, simple, and accessible via mobile phones, making it easier forthe community to independently monitor their health conditions. This activity demonstratesthat simple digital innovations can be a promotive and preventive solutionin community physiotherapy to reduce the risk of metabolic diseases.